1989
DOI: 10.1104/pp.89.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Induction of Na+/H+ Exchange Activity in Barley Root Tonoplast

Abstract: Na+/H exchange activity in barley (Hordeum vulgare cv CM-72) root tonoplast was induced by Na+ even in the presence of inhibitors of protein synthesis. Induction occurred with a half-time of only 15 minutes. When salt-treated roots were transferred to a nutrient solution containing no Nat, the activity disappeared with a similar time course. The data suggest that Na+/H+ exchange was due to activation of an existing protein rather than to de novo protein synthesis.Buildup of salts in the soil is a major problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 10 publications
2
50
0
1
Order By: Relevance
“…Within 15 min of exposure to saline conditions, an Na+/H+ exchange process is activated so that K+ can be pumped across the cell membrane (Watad et ai., 1986) and Na+ can be pumped into tonoplasts (Binzel et al, 1988;Garbarino and DuPont, 1989). Over the course of several days, the ratio of glycolipids to phospholipids can increase (Hirayama and Mihara, 1987), permitting more solutes to enter the cell and thus facilitate water entry, while the overall concentration of osmoprotectants including sugars, proline, and organic acids rises (Binzel et al, 1987;LaRosa et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Within 15 min of exposure to saline conditions, an Na+/H+ exchange process is activated so that K+ can be pumped across the cell membrane (Watad et ai., 1986) and Na+ can be pumped into tonoplasts (Binzel et al, 1988;Garbarino and DuPont, 1989). Over the course of several days, the ratio of glycolipids to phospholipids can increase (Hirayama and Mihara, 1987), permitting more solutes to enter the cell and thus facilitate water entry, while the overall concentration of osmoprotectants including sugars, proline, and organic acids rises (Binzel et al, 1987;LaRosa et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, for example, in Atriplex nummularia (Braun et al, 1988) and Dunaliella salina (Katz et al, 1991), the Na+/H+-antiport appears to be associated with the plasmalemma, but in the majority of studies the antiport activity has been found in the tonoplast, where it appears to be responsible for the uptake and sequestration of sodium into the vacuole, thus preventing the accumulation of toxic ions in the cytosol. Evidence for the importance of the tonoplast Na+/H+-antiport in salt tolerance is provided by the discovery that the antiport can be activated by salt treatment in barley (Gabarino and Dupont, 1989) and in P. maritima (Staal et al, 1991), although it is not yet clear how activation is achieved.…”
mentioning
confidence: 99%
“…However, Streeter (27) estimated the NH4+ concentration in soybean nodule cytosol to be 'essentially nil. ' The cytoplasmic NH4' concentration may also be important with respect to pH gradients between intracellular compartments; millimolar concentrations of NH4' can collapse transmembrane pH gradients in vitro (3). Solutions of NH3 have been shown to rapidly and dramatically increase intracellular pH (15,21).…”
mentioning
confidence: 99%